A Scotland without poverty : the Joseph Rowntree Foundation's manifesto briefing for a prosperous and poverty free Scotland.: the Joseph Rowntree Foundation's manifesto briefing for a prosperous and poverty free Scotland. ([2016?]) - Joseph Rowntree Foundation,
No abstract available